2006
DOI: 10.4314/sinet.v28i2.18254
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of cassava wastewater effluents to African catfish: <i>Clarias gariepinus</i> (Burchell, 1822)

Abstract: The relative lethal and sublethal toxicity of cassava wastewater effluents from a local food factory were investigated on Clarias gariepinus fingerlings using a renewable static bioassay. The physico-chemical characteristics of the cassava wastewater effluents showed a number of deviations from the standards of the Federal Environmental Protection Agency (FEPA) on the guidelines for effluent discharges. Considering the pollutants of the effluent, cyanide (CN) is suspected to be primarily responsible for the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
23
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 5 publications
10
23
1
Order By: Relevance
“…namely: active. fatigue and collapse.This result was in line with the findings of Adewoye et al (2005) and Soni et al (2006) who reported that erratic behavioural responses of the test organisms were resulted from high concentration of toxicants found in the industrial effluent. As the authors reported that as the experiment progressed, erratic behavioural response of the test organisms was reduced, and eventually they stopped swimming.…”
Section: Discussionsupporting
confidence: 82%
“…namely: active. fatigue and collapse.This result was in line with the findings of Adewoye et al (2005) and Soni et al (2006) who reported that erratic behavioural responses of the test organisms were resulted from high concentration of toxicants found in the industrial effluent. As the authors reported that as the experiment progressed, erratic behavioural response of the test organisms was reduced, and eventually they stopped swimming.…”
Section: Discussionsupporting
confidence: 82%
“…The synthetic resin effluent examined in this work was found to be high in total suspended solid (TSS), low biochemical oxygen demand (BOD), low dissolved oxygen (DO), low total dissolved solids (TDS) and high lead and cyanide content which shows the effluent to be toxic for discharge into the aquatic environment. The abnormalities observed prior to mortality is an indication of depleted oxygen content due to higher demand for oxygen, this corresponds to the findings of Adewoye et al, (2005) that the observed characteristics features may have resulted from the organic loads in the wastewater and to different concentrations of toxicants. The high degree of lead and cyanide found in the effluent may have contributed a significant synergistic effects which resulted in the breakdown of vital metabolic functions that led to high mortality observed especially in the highest concentrations and this corresponds to the discovery of Van-Dyk et al, (2007) that the harmful effects of heavy metals pollution of fish depend on the duration of the exposure (chronic or acute) and the concentration level of the specific metal.…”
Section: Physicochemical Characteristics Of Syntheticmentioning
confidence: 94%
“…The 24-h LC 50 value of neem leaf extract for Prochilodus lineatus was found to be 4.8gL −1 (Winkaler et al, 2007). Adewoye et al, (2005) noted that at 96-h LC 50 concentration, the fitness of the natural population of an aquatic environment would be relatively impaired and as the concentration increases, the mortality rate also increases. The 96h LC 50 of 0.355187mg/L implies that at this concentration of the effluent in the aquatic environment, half of the entire natural population will become dead.…”
Section: Physicochemical Characteristics Of Syntheticmentioning
confidence: 99%
“…A problem with most of these methods is that beneficial nutrients, such as B vitamins (thiamine, riboflavin and niacin), β-carotene (a source of vitamin A) and vitamin C, can be leached out or destroyed, which reduces the already low nutritional value of cassava [33]. There is also evidence that waste water from cassava processing (e.g., for starch production) can be toxic to the environment, with significant toxicity in fish reported [124,125].…”
Section: Cyanogens In Cassava: Impacts On Human Healthmentioning
confidence: 99%